Análisis de los perfiles profesionales del departamento de comunicación de la UTB 2021 - Arreaga Rodríguez, Vicente Nahúm (2023)
The case study analyzed which were the professional profiles of the communication department of the Technical University of Babahoyo and its effectiveness in carrying out activities that relate to the institutional environment, to analyze the role of communicator and identify what are the competencies and skills, knowledge, they should know as communication professionals to perform at the time of practice in the communication department. With the use of the synthetic and descriptive analytical method, the objectives were fulfilled, the research tools used were interviews and the survey of professionals working in the area of communication was used for data collection. The results indicate that communication professionals must have knowledge, skills and competencies for optimal job performance, and it is important that they are innovative and are constantly learning because in a HEI like the Technical University of Babahoyo respond to the demands and requirements, it is very important due to the constant evolution and demand of the institutions.